Visual rehabilitation and outcomes for ectasia after corneal refractive surgery - Woodward, Maria (2008)
PURPOSE: To analyze the visual outcomes and method of final visual correction in eyes with corneal ectasia after laser in situ keratomileusis (LASIK) or photorefractive keratectomy (PRK). SETTING: Emory University Department of Ophthalmology and Emory Vision, Atlanta Georgia, USA. METHODS: This retrospective review comprised 74 eyes of 45 patients with corneal ectasia after LASIK (72 eyes) or PRK (2 eyes). Outcomes included postoperative uncorrected visual acuity (UCVA), best spectacle-corrected visual acuity (BSCVA), best corrected visual acuity (BCVA), and refraction; method of final visual correction; and time to rigid gas-permeable (RGP) contact lens failure. RESULTS: Corneal ectasia developed a mean of 19.2 months after surgery. Postoperatively, the mean UCVA was 20/400, the mean BSCVA before ectasia management was 20/108, and the mean BCVA was 20/37. After ectasia management, the final BCVA was 20/40 or better in 78% of eyes. Final visual correction was achieved with RGP lenses in 77% of eyes, spectacles in 9%, collagen crosslinking in 3%, intracorneal ring segments in 1%, and penetrating keratoplasty (PKP) in 8%. Two eyes with intracorneal ring segments required segment explantation and subsequent PKP. One eye that had PKP had a graft-rejection episode; there were no graft failures. Two eyes (3%) did not require a visual device to improve visual acuity. The mean time to successful RGP lens wear was 24.8 months; 80% of cases initially managed with RGP lenses were successful with this form of treatment. CONCLUSIONS: The majority of eyes developing postoperative corneal ectasia achieved functional visual acuity with RGP lens wear and did not require further intervention. Penetrating keratoplasty can usually be postponed or avoided by alternative methods of visual rehabilitation; however, PKP, when necessary, can provide good visual outcomes.